Structural Design and Kinematic Analysis of Humanoid Robot Arms - Yang Yakun; Zhang Xiaojun; Qin Kang (Jixie chuandong)
Aiming at the problem that human beings are prone to fatigue when they repeatedly perform a single action in the performance test of the driver attention monitoring system, a humanoid robot arm is designed to simulate the driver's behaviors such as answering and making handsets and smoking. Firstly, based on the exoskeleton design method, the structure of the robot arm and the bionic hand is designed. Secondly, the improved D-H method is used to establish the kinematics model of the manipulator; the forward and inverse kinematics are solved, and the workspace is analyzed; the dynamics simulation of the robot arm is carried out in Adams software to obtain its motion characteristics and load characteristics. The simulation results show that the structural design of the manipulator is reasonable, and the selection of joint flexible actuators meets the requirements.